Are Firms Hiring Enough Workers? Firm-level Evidence from Finland’s Manufacturing and Service Industries - Kuosmanen, Natalia; Kuosmanen, Timo; Pajarinen, Mika (Finland, 2026)
Microeconomic theory posits that in competitive markets, wages are determined by the marginal revenue product of labor. This study empirically tests this theoretical prediction using comprehensive firm-level register data from Finland’s manufacturing and service industries in years 2000–2022. We estimate the marginal products of labor based on production functions estimated using both parametric and nonparametric methods, including convex expectile regression and its control function extension. We then compare the estimated marginal products with estimated marginal costs of labor. The estimated marginal products systematically exceed the marginal costs in all industries, which suggests that most Finnish firms are understaffed, employing less than profit-maximization in a competitive market would require. We find that marginal products are most closely aligned with marginal costs in traditional service sectors. In contrast, the marginal products exceed the marginal costs most notably in capital and knowledge-intensive manufacturing industries, such as pharmaceuticals, metal industries, and information services. Our findings reveal persistent and heterogeneous wage-productivity gaps in Finland despite the fact that Finland has strong unions and labor market institutions.